OECD guidance for national compliance monitoring programmes: carrying out study audits - Calder, Louise (Henry Stewart Talks, 2012)
Objective and purpose of study audits, How to select studies, Performing study audits, The facility and the inspectors, Approach variation, Review question and listen, Traceability and reproducibility, Checklist, Thinking, asking & investigating problems, Auditors & Inspectors, Attitudes and behaviours, Reporting, Departures from the GLP principles